2012
DOI: 10.1242/jcs.088047
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics within tetraspanin pairs affect MHC class II expression

Abstract: SummaryLate endosomal multivesicular bodies (MVBs) are complicated organelles with various subdomains located at the limiting membrane and the internal vesicles (ILVs). ILVs accumulate tetraspanins such as CD63 and CD82 that might form protein assemblies, including major histocompatibility complex class II (MHC-II) and its chaperone human leukocyte antigen (HLA)-DM. Here, we studied the effect of four late endosomal tetraspanin proteins on MHC-II expression. Silencing CD9, CD63 and CD81 enhanced MHC-II express… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 37 publications
1
23
0
2
Order By: Relevance
“…Although the absence of CD9 in MoDCs did not alter the expression of adhesion molecules or the IS formation, it significantly impaired CD4 ϩ T cell activation, suggesting that CD9 regulates Ag presentation. This effect does not seem to be related to an impairment of MHC-II coupling to antigenic peptides, since it was previously shown that CD9 knockdown in DC does not affect MHC-II peptide loading (44). In this regard, we did not observe differences in Ag proteolytic processing in CD9 KO MoDCs.…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…Although the absence of CD9 in MoDCs did not alter the expression of adhesion molecules or the IS formation, it significantly impaired CD4 ϩ T cell activation, suggesting that CD9 regulates Ag presentation. This effect does not seem to be related to an impairment of MHC-II coupling to antigenic peptides, since it was previously shown that CD9 knockdown in DC does not affect MHC-II peptide loading (44). In this regard, we did not observe differences in Ag proteolytic processing in CD9 KO MoDCs.…”
Section: Discussionsupporting
confidence: 54%
“…These molecules associate with tetraspanins CD63 and CD82 on both MIIC subdomains (41,42,44), with CD63 stably interacting with MHC-II and CD82 with HLA-DM (44). CD63 regulates peptide-loaded MHC-II surface expression and could act as a cochaperone (44). We have investigated the colocalization of MHC-II with different markers of intracellular vesicles.…”
Section: Discussionmentioning
confidence: 99%
“…Within endosomal compartments, CD9, CD63, and CD81 all were important for controlling surface expression of MHC II (37). Tetraspanins can also associate with class II molecules on the surface (38).…”
Section: Lipid Domains and Other Microdomainsmentioning
confidence: 99%
“…An enlargement of gB/CD63/DR-costained vesicles was observed in some cell types, usually upon the overexpression of gB [19,23]. In addition, CD63 stably interacts with MHC II at MVB, including ILV, and controls MHC II expression [46]. Therefore, the CD63-MHC II association may be important for exosomal MHC secretion.…”
Section: Alphaherpesvirus Gb Homologs Affect Mhc Class Ii-cd63 Traffimentioning
confidence: 99%